RANCANG BANGUN MINIATUR CONVEYER BELT CERDAS BERBASIS MIKROKONTROLER AT89S51 - siringo ringo, kolombus; SAMAR, (Jurnal Sains dan Teknologi ISTP, 2025)
Transporting goods from one place to another and at the same time calculating the quantity is still done manually in general. Transporting and counting goods manually is not economical because of the limited ability of employees, so tools are needed, for example using a conveyer belt. The conveyer belts currently used in industry generally do not work automatically in counting and transporting goods. To make the conveyer belt work automatically, sensors and controls based on the AT89S51 microcontroller are needed. The AT89S51 microcontroller functions as a central controller for all parts of the conveyer belt in receiving data from sensors, processing it, and sending it to the drive amplifier to control the servo motor. The servo motor drives the conveyer belt. To detect goods on the conveyer, a motion sensor is used in the form of infrared light that is emitted by an LED onto a photo diode. If there is an object blocking the emission of infrared light from the LED to the photo diode then a low voltage comes out (bit 0) and conversely there is no object blocking it then a high voltage comes out (bit 1). The number of items that pass through the infrared rays is displayed in seven segments. The command button functions to notify the microcontroller of the number of items to be transported and counted. If the number of items counted and moved is sufficient as specified, the conveyer stops automatically.